Consumer surplus analysis using the Travel Cost Method (TCM) at the Petrus Kafiar Beach tourist attraction, Manokwari Regency, West Papua - Yuyun Rahayu; Ismi Haryati (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
This study aims to determine the economic value of tourism objects and whether there is a consumer surplus at the Petrus Kafiar beach based on the Travel Cost Method (TCM). The consumer surplus value is obtained by using the Individual Travel Cost Method (ITCM) approach and willingness to pay to calculate the willingness to pay of tourists visiting Petrus Kafiar Beach. The value of WTP obtained is Rp. 23,358.21 per person per visit. Meanwhile, the average WTP (willingness to pay) per year for one visit is only Rp. 5,491.23. The results of the integral calculation to find the consumer surplus of visitors to the Petrus beach tourism object, the consumer surplus is ranged from Rp. 5,201.5 to Rp. 10,403.91 per individual/visit.